2019
DOI: 10.3390/polym11071155
|View full text |Cite
|
Sign up to set email alerts
|

Design and Application of Highly Efficient Flame Retardants for Polycarbonate Combining the Advantages of Cyclotriphosphazene and Silicone Oil

Abstract: A novel flame retardant (HSPCTP) was successfully designed and incorporated into a polycarbonate (PC) matrix. Combining the advantages of cyclotriphosphazene and silicone oil, PC/HSPCTP composites passed UL-94 V-0 rating testing with only 3 wt% HSPCTP, and their LOI value increased from 25.0% to 28.4%. The findings showed that HSPCTP exhibits both gas-phase and solid-phase flame-retardant effects. Furthermore, the incorporation of HSPCTP into PC could suppress the release of smoke. Finally, the flame-retardant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…Several cyclotriphosphazene derivatives with excellent properties have been synthesized by replacing Cl atoms of HCCP [ 25 , 26 ]. Before this, halogen was used as a flame retardant substance, but it is reported that these halides release toxic and corrosive substances during their decomposition and cause environmental problems [ 27 ]. Therefore, it is necessary to develop halogen-free and environment-friendly flame retardants to improve flame retardancy.…”
Section: Introductionmentioning
confidence: 99%
“…Several cyclotriphosphazene derivatives with excellent properties have been synthesized by replacing Cl atoms of HCCP [ 25 , 26 ]. Before this, halogen was used as a flame retardant substance, but it is reported that these halides release toxic and corrosive substances during their decomposition and cause environmental problems [ 27 ]. Therefore, it is necessary to develop halogen-free and environment-friendly flame retardants to improve flame retardancy.…”
Section: Introductionmentioning
confidence: 99%
“…Flame retardant bisphenol-A based polycarbonate (PC) has been widely used in the electronic industry thanks to its balanced physical properties and flame retardancy [1][2][3]. The flame retardancy of PC has been frequently accomplished by incorporating a small amount of sulfonate salts [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For the preparation of cyclotriphosphazene-containing materials, hexachlorocyclotriphosphazene is commonly used as starting precursor, followed by the substitution of chlorine atoms using (mostly) organic side groups. Moreover, cyclotriphosphazenes can be functionalized for example with various alkoxysilanes to increase their introduction in the sol-gel process [ 19 , 20 , 21 ], particularly, for various promising applications as bio-applied dendrimers [ 17 ], in photoelectronics [ 22 ] and as flame retardants [ 23 ].…”
Section: Introductionmentioning
confidence: 99%